Urinary urodilatin levels in patients with renal salt wasting syndrome as a possible new diagnostic marker. A pilot study - Della Corte, Vittoriano; Agnello, Luisa; Norrito, Rosario; Cataldi, Marco; Del Ben, Fabio; Pecoraro, Rosaria; Maida, Carlo; Gambino, Caterina Maria; Daidone, Mario; Giglio, Rosaria Vincenza; Ciaccio, Marcello; Tuttolomondo, Antonino (Frontiers in Pharmacology, 2025)
BackgroundRenal Salt Wasting Syndrome (RSW) is a clinical syndrome with laboratory characteristics completely overlapping with the syndrome of inappropriate antidiuretic hormone secretion (SIADH). No studies have yet investigated the potential role of urodilatin as a diagnostic marker or its involvement in the pathogenesis of RSW.MethodsWe performed a retrospective observational case-control study, the patients were divided into 3 groups: a group of hyponatremic patients with RSW (cases) and two control groups (subjects without hyponatremia and subjects with hyponatremia from other causes). Main outcomes were assessing the differences in urinary urodilatin values in patients with RSW compared to both control groups and to evaluate the diagnostic power of urodilatin with the analysis of ROC curves.ResultsPatients with RSW display significantly higher mean urodilatin levels than both patients with (median 5.46 vs. 0.57 ng/mL, p = 0.006) or without hyponatremia (median 5.46 vs. 0.27 ng/mL, p < 0.001). Diagnostics performances of mean urodilatin levels for RSW diagnosis were evaluated by ROC curve, AUC was 0.94 (95%CI 0.86–1.00).ConclusionThis case-control study has shown interesting results regarding the dosage of urinary urodilatin in patients with RSW, with potentially clarifying implications both regarding the pathogenesis of this syndrome and regarding the diagnosis and therefore the clinical management of patients.